Serial QuantiFERON-TB Gold testing in patients with psoriasis treated with ustekinumab. - Chuan-Yu Hsiao; Hsien-Yi Chiu; Ting-Shun Wang; Tsen-Fang Tsai (PLoS ONE)
Background There is increasing concern about the risk of latent tuberculosis infection (LTBI) reactivation during the use of biologics for psoriasis. Although ustekinumab had been documented with low risk of tuberculosis, the long-term follow-up of LTBI as determined by QuantiFERON-TB Gold (QFT-G) testing in patients treated with ustekinumab is limited. Objectives This study aims to use serial QFT-G testing as a screening method for detecting LTBI in patients with psoriasis from an intermediate tuberculosis burden country. Methods This retrospective review investigated 134 psoriatic patients in whom ustekinumab was prescribed for at least one year between 2010 and 2016 in National Taiwan University Hospital. All patients underwent annular QFT-G testing during ustekinumab therapy. Results Among the 134 enrolled patients, baseline LTBI rate was 13.4% (18/134). Indeterminate QFT-G result was noted in 5.2% (7/134) of patients and 71.4% (5/7) of them turn to be QFT-G negative during the next testing. 81.3% (109/134) of patients had a negative QFT-G at baseline and the seroconversion rate was 7.3% (8/109) in the serial QFT-G. All the patients in the conversion group were referred to a pulmonologist for evaluation and 81.5% (22/27) of them underwent chemoprophylactic therapy while on ustekinumab. No active TB infection was noted during further follow-up with or without chemoprophylaxis. Conclusions This study revealed that psoriatic patients receiving long-term ustekinumab therapy had a low QFT-G conversion rate (7.3%). The clinical significance of QFT-G conversion remains controversial and needs larger scale trials to investigate.